Determinant of Islamic Banks on the World Capital Structure - Wardana, Guntur Kusuma; Noer Aisyah Barlian (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
Economic competition is increasing nationally and even globally. This encourages leaders of the banking industry to develop strategies, achieve the vision and mission, then make policies and activity programs that support banking achievements. Generally, there are various factors that can affect the capital structure; including bank size, profitability and asset growth. The purpose of the study is to determine the influence of bank size, profitability and asset growth on the capital structure of Islamic banking in the world partially and simultaneously. Sample of this studi is 18 Islamic banks in the world has gain by purposive sampling method. The results represent that bank size and asset growth had a significant positive effect on the capital structure. ROA had a significant negative effect on the capital structure then ROE and PER did not have a significant effect on the capital structure of Islamic banks in the world. Simultaneously, bank size, ROA, ROE, PER and asset growth have a significant effect on the capital structure of Islamic banks in the world.